Toward productivity improvement in electrical engineering documentation - Zhou, Jingyang; Love, Peter; Matthews, Jane; Carey, Brad; Sing, C.; Edwards, D. (2015)
Purpose – The purpose of this paper is to determine the unproductive time and additional cost to re-engineer a safety control system for a Floating Production Storage Offloading vessel that was originally engineered and documented in computer-aided design (CAD). Design/methodology/approach – The “As-Built” drawings contained numerous errors and omissions, which resulted in a “requests for information” being raised and productivity rates reduced – these costs and productivity losses are quantified. The use of CAD to originally engineer and document the safety control system was found to be inefficient as a 1:n relationship existed. Systems Information Models (SIMs) presents an alternative method to produce engineering documentation for the safety control system; where a 1:1 relationship is created between the model and the real objects. By constructing a 1:1 model, information redundancy can be eliminated, which reduces the propensity for errors and omissions to be made by engineers. Findings – The use of a SIM to re-engineer and document the new safety control system resulted in significant productivity benefits being achieved. Consequently, it is proffered that a paradigm shift from a 1:n to 1:1 perspective is required for engineering electrical and instrumentation systems so as to ameliorate the quality of documentation produced and productivity. Originality/value – The paper concludes by suggesting that future research is required to examine how processes and procedures can be re-designed to accommodate the use of a SIM.